Analisis Populasi Amfibia Anura di Kawasan taman Hutan Raya Bukit Sari Provinsi Jambi : Analysis of population of Amphibian Anura in Bukit Sari Grand Forest Park Jambi Province - Wulan, Cory; Nugroho, Singgih; Khabibi, Jauhar (Jurnal Silva Tropika, 2023)
ABSTRACT Bukit Sari Grand Forest Park is one of the conservation areas that is a habitat for amphibians. Habitat conditions and quality certainly affect the diversity of amphibian species. This study aims to analyze the population and compare the diversity of amphibian species of the order anura based on different habitat types and identify the habitat conditions of amphibians of the order anura in Bukit Sari Grand Forest Park. The research method used in this research is Visual Encounter Survey in data collection carried out on habitat types (natural forests, oil palm plantation transitions, rubber plantation transitions and open area transitions). The data obtained were analyzed using the species diversity index (Shannon Wiener), community similarity index, eveness index and species richness index. Based on the results of anura research that has been carried out on 4 habitat types in the Bukit Sari Grand Forest Park, 149 individuals and 16 species from 5 families were found, namely Bufonidae, Dicroglossidae, Microhylidae, Ranidae and Rhachoporidae. The most common type found is from the Dicroglossidae family, Limnonectes macrodon which was found 31 individuals. The amphibian diversity index in Bukit Sari Grand Forest Park is classified as medium category while the species richness index is classified as a low category. Keywords: Amphibians, anura, Bukit Sari Grand Forest Park, diversity, population Â  ABSTRAK Taman Hutan Raya Bukit Sari merupakan salah satu kawasan konservasi yang menjadi habitat amfibi. Kondisi dan kualitas habitat tentunya mempengaruhi keanekaragaman jenis amfibi. Penelitian ini bertujuan untuk menganalisis populasi dan membandingkan keanekaragaman jenis amfibi ordo anura berdasarkan tipe habitat yang berbeda serta mengidentifikasi kondisi habitat amfibi ordo anura di Tahura Bukit Sari. Metode penelitian yang digunakan dalam penelitian ini adalah VES (Visual Encounter Survey) dalam pengambilan data yang dilakukan pada tipe habitat (hutan alam, transisi perkebunan kelapa sawit, transisi perkebunan karet dan transisi areal terbuka). Data yang diperoleh dianalisis dengan menggunakan indeks keanekaragaman jenis (Shannon Wiener), indeks kesamaan komunitas, indeks kemerataan jenis dan indeks kekayaan jenis. Berdasarkan hasil penelitian anura yang telah dilakukan pada 4 tipe habitat di kawasan Tahura Bukit Sari, ditemukan 149 individu dan 16 jenis dari 5 famili, yaitu Bufonidae, Dicroglossidae, Microhylidae, Ranidae, dan Rhachoporidae. Jenis yang paling banyak ditemukan adalah dari famili Digroglosidae yaitu Limnonectes macrodon yang ditemukan sebanyak 31 individu. Indeks keanekaragaman amfibi di Tahura Bukit Sari menunjukkan kategori sedang sedangkan indeks kekayaan jenis di Tahura Bukit Sari tergolong dalam kategori rendah. Â  Katakunci: Amfibi, anura, keanekaragaman, populasi, Taman Hutan Raya Bukit Sari